The Territorial Limitation Dispute and Its Settlement Between Peru and Chile (The Digest: Journal of Jurisprudence and Legisprudence, 2021)
In a country usually consists of an area in the form of land, an area in the form of oceans, and airspace. Sometimes these areas must be directly adjacent to other areas of the country, with this the State should have responsibility regarding the boundaries of its country to determine and claim that the position and boundaries are the property of its country, and are required to register the territory with the United Nations. The sea border dispute that occurred between Chile and Peru began when the two countries were adjoining territories after Bovilia surrendered its maritime territory to Chile resulting from losing the Pacific War in 1883. Then in 1947 Peru and Chile stated in their own way that sovereignty over the sea, which is 200 miles along the coast of each of the Chilean and Peruvian countries. The Peruvian president denies that the maritime zone between Chile and Peru has never been based on legal agreements. But on the other hand Chile claims that both parties have agreed to limits in the sea zone measured from the shoreline that runs along parallel latitudes